Market orientation and organizational performance :|bthe impact of service quality a study on hotel industry in Malaysia - Chin, Chee Hua. (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The general objective of this research was to examine the relationship between market orientation and organizational performance. In addition, service quality was included as a moderator. This study was conducted on hotel industry in Malaysia and 187 set of samples were collected randomly from 55 3 -stars and above hotels in Malaysia. Analyzing tools such as Statistical Package for Social Science (SPSS) 18.0 for Windows and SmartPLS 2.0 were used to analyze the data collected. Tests such as confirmatory factor analysis, convergent validity, discriminant validity and reliability were carried out to assess measurement model. Besides, t -Value test was used to assess the structural model. The outcomes from the analyses have demonstrated partially support for the hypotheses. The results showed that market orientation was not significantly influence organizational performance whereas exists of service quality moderated the relationship between market orientation and firm performance. Thus, this study may increase managers understanding toward the importance of service quality, market orientation practices that lead to better organizational performance. This paper enhances both scholars' and practitioners' understanding about the influence of service quality as a moderator in moderating the relationship between market orientation and organizational performance.